Licenciada en ciencias de la educación básica - Armijos Reyes, Geraldine Marisol; Aguilar Avecicha, María Gabriela (Machala, Universidad Técnica de Machala, 2022)
The current society has progressed, this means that education and traditional methods no longer create a desire to learn, but rather boredom and negativity, so new and better strategies are needed for the teaching-learning process, one of them is through the application of educational tools. Therefore, the theme of the work is: Toy libraries for the teaching and learning of mathematics in second grade EGB students, Tula Pérez School, period 2021; where an analysis is provided in relation to games in learning, providing insight into the role that games can play as more educational institutions use them as a way of teaching. The methodology based on the mixed approach was used, which consists of the qualitative one that allows the collection of the data obtained from the investigation and the quantitative one because data was collected that was tabulated in tables, analyzed with graphs and interpreted through personal analysis. Exploratory type research, descriptive, explanatory research and finally the field modality was also applied because information was obtained directly from the students and teachers in their own school workplace and with which it was allowed to achieve the results obtained. of the objectives outlined in the work. As a result of the work, it was obtained within the analysis of the interview that the teacher does not encourage gamification in the area of the problem, but considers that it helps to develop abilities and skills and in turn allows them to relate to other classmates and promote confidence. It was also identified that teachers only use their classrooms for the teaching-learning process, so there is no relationship with the natural environment and they also do not develop their social skills because the teacher does not implement cooperative games or collaborative work that allows the student to develop their skills and attitudes. Likewise, due to the problems that have been identified within the "Tula Pérez" School, it is urged that there be an efficient solution so that there is an improvement in the academic performance of the students, given that the students do not understand the subject. of mathematics, so the teacher does not implement teaching materials and there is no prior motivation in the class, therefore there is a low academic performance in the second-grade children, for this reason a requirement matrix was developed which will respond to the problem. As general conclusions of the investigation, it was found that the intraus spaces used by the teacher for teaching in the area of mathematics, because the students can be in a single space and the teacher observes and controls the student's behavior and learning. In addition, it was possible to deduce that the toy libraries as recreational spaces are suitable for a better learning of all students, which allows an integral development that facilitates understanding and promotes significant learning; so, it is important to implement the toy libraries in the classes.
La actual sociedad ha progresado, esto encierra que la educación y métodos tradicionales ya no crean ganas de aprender, sino aburrimiento y negatividad, por lo que se necesitan nuevas y mejores estrategias para enseñar y aprender de mejor manera mediante el empleo de herramientas educativas innovadoras. Por ello, el tema del trabajo es: Ludotecas para la enseñanza y aprendizaje de las matemáticas en estudiantes de segundo grado EGB, escuela Tula Pérez, periodo 2021; donde se proporciona un análisis en relación con los juegos en el aprendizaje, proporcionando una idea del papel que pueden desempeñar los juegos a medida que más instituciones educativas los utilizan como una manera de enseñanza. Se utilizó la metodología fundamentada en el enfoque mixto, que consta del cualitativo que permite la recolección de información, y cuantitativo porque se recopilan datos que fueron tabulados en tablas, analizados con gráficas e interpretados mediante el análisis personal. También se aplicó la investigación de tipo exploratorio, la investigación descriptiva, explicativa y para finalizar la modalidad de campo porque se obtuvo información directamente de los estudiantes y de los docentes en su propio lugar de trabajo escolar y con los cuales se permitió alcanzar los resultados obtenidos de los objetivos trazados en el trabajo. Como resultado del trabajo se obtuvo dentro del análisis de la entrevista que el docente no fomenta la gamificación en el área de la problemática, pero considera que ayuda a desarrollar habilidades y destrezas y a su vez permite relacionarse con los demás compañeros y promover la confianza. También se identificó que los docentes solamente utilizan sus aulas para enseñar al estudiante por lo que no hay una relación con el medio natural y tampoco desarrollan sus habilidades sociales porque el docente no implementa juegos cooperativos o trabajos colaborativos que permita al estudiante desarrollar sus destrezas y actitudes. Asimismo, debido a los problemas que han sido identificados dentro de la escuela Tula Pérez se exhorta que haya una solución eficiente para que exista un mejoramiento en el rendimiento académico de los educandos, en vista de que los estudiantes no comprenden los contenidos matemáticos por lo que el docente no implementa materiales didácticos y no existe una motivación previa en la clase, por lo tanto existe un bajo desempeño académico en los niños de segundo de básica, por esta razón se elaboró una matriz de requerimiento la cual va a dar respuesta a la problemática. Como conclusiones generales de la investigación se comprobó que los espacios intra áulicos empleados en la enseñanza matemática, debido a que los estudiantes pueden estar en un solo espacio y el docente observa y controla la conducta y aprendizaje del estudiante. Además, se pudo deducir que las ludotecas como espacios lúdicos son acordes para un mejor aprendizaje de todos los estudiantes el cual permite un desarrollo integral que facilita la comprensión y promueve aprendizajes significativos; por lo que es importante implementar las ludotecas en las clases.
Keywords: LUDOTECA; ENSEÑANZA; APRENDIZAJE; MATEMATICA; ESTUDIANTE